"L'ENFER, C'EST LES AUTRES": Proximity as an Ethical Problem during COVID‐19. (26th August 2021) - STRONG, THOMAS; TRNKA, SUSANNA; WYNN, L. L.
ABSTRACT: During the COVID‐19 emergency, people around the world are debating concepts like physical distancing, lockdown, and sheltering in place. The ethical significance of proximity—that is, closeness or farness as ethical qualities of relations (Strathern 2020)—is thus being newly troubled across a range of habits, practices, and personal relationships. Through five case studies from Australia, Ireland, New Zealand, South Africa, and the United States, contributors to this Colloquy shed light on what the hype of the pandemic often conceals: the forms of ethical reflection, reasoning, and conduct fashioned during the pandemic.